Chondral lesion of the patella in a junior football player: chondral-only fragment fixation - Seiça, Emanuel C.; Armada, Lucas; Canhoto, Joana; Santos, Hugo Vaz dos; Viegas, Rui; Barbosa, Luís (International Journal of Research in Orthopaedics, 2024)
Chondral lesions of the patella are a relatively common pathology that can cause pain and impairment in active young individuals. These lesions can have lifelong consequences, with increased risk of osteoarthritis in some cases. Surgical excision of medium to large fragments is associated with poor long-term outcomes. There is a general belief that fixation of purely chondral lesions in the absences of subchondral bone is associated with low integration rates, however recent case reports and basic science studies have been challenging this belief. In this case report, we describe a young patient with a chondral lesion of the patella and a fragment without subchondral bone, who underwent open fragment reduction and fixation using bioabsorbable pins. The patient had a successful outcome with significant fast improvement in pain and function and full return to practice. This case highlights the potential benefits of conservative surgical management with preservation of the native cartilage, even in the absence of subchondral bone, especially in the young active patient.